Autonomy in language learning - Hussein, Abdul Kadir; Che Haron, Sueraya (International Institute for Science, Technology & Education (IISTE), 2012)
This study investigated the practice of autonomy in Arabic language learning among Arabic language learners at the International Islamic University Malaysia. The samples were 179 students ranging from level 4-5 and of all specializations at the university. The data were collected using survey adapted from Jianping XU (2009) consisting 22 items and 5 Likert scales. Descriptive statistics was used to analyze the data. The results revealed that learners could be described as autonomous learners as they demonstrated positive responses towards most of the items in the survey. In other words they have the capabilities to take charge of their own learning except in several items especially when it comes to self-productive activities such as: communication, writing and translation.